Expression of gene coding endoglucanase GH5-4 derived from meagenomic DNA data of bacteria in goats rumen in \(Escherichia coli\) - Dang, Nguyen Hai; Huyen, Do Thi; Kien, Nguyen Thi; Hoa, Ha Thi Thuy; Giang, Le Quynh; Khoa, Dao Trong; Hai, Truong Nam (Academia Journal of Biology, 2021)
Glycoside Hydrolase family 5 (GH5) members share a broad range of enzymatic activities on oligosaccharides, polysaccharides and glycoconjugates from a wide range of species. The subfamily 4 (GH5-4) is enriched in some broad-specificity endo-β-1,4-endoglucanases (EG). From metagenomic DNA data of bacteria in Vietnam goats’ rumen, a gene GL0361920 coding for endoglucanase GH5-4 was mined and selected for expression in Escherichia coli. Firstly, the codons of the gene were optimized and the codon optimized gene (eg3) was artificially synthesized and inserted into pET21a(+) at NdeI-XhoI positions for expression in E. coli. The results of the gene expression in five E. coli strains analyzed by SDS-PAGE showed that the recombinant endoglucanase (EG3) coded by eg3 was the best expressed in BL21, Origami strains, was not expressed in JM109 strain and expressed at very little amount in C43 and Rosetta strains. Among LB, TB, LB, SB, TBD media, the recombinant BL21 strain grew best at TB medium and produced total EG3 higher than the other media. The inducer IPTG gave a negative effect on the growth of the cells but the increase concentration of IPTG from 0.05 mM to 0.9 mM did not increase the negative impact on the cell mass and produced EG3 was nearly the same at the different IPTG concentrations. At 25 oC, in the TB medium containing 0.1 mM IPTG, the recombinant E. coli BL21 strain harboring pET21-eg3 produced about half of endoglucanase EG3 in a soluble form exhibiting activity hydrolyzing CMC substrate. At the OD600=10, soluble EG3 accumulated in the recombinant E. coli BL21 strain had the activity of 0.22 ± 0.006 U/ml.